Documents. L'Union des journalistes de Yougoslavie. Medunarodna politika
Engl. ed.: Documents. Federation of Yougoslav journalists (ZO 30609) - German ed.: Dokumente. Journalistenverband Jugoslawiens (ZO 30614).